A pesquisa no Curso de Pedagogia na perspectiva do corpo docente. - Castro, Edna Ribeiro (2008)
In view of the importance that research has acquired in teacher’s formation current discussions, this study proposes to investigate factors that interfere in the research practice of the teachers of the Pedagogy Course of the Center of Superior Studies of Caxias (CESC), State University of Maranhão (UEMA). The study was dedicated to discuss the difficulties and possibilities for the development of research by teachers as a practice inherent to teaching as a way to follow Pedagogy National Curricular Directions. The study objectified: a) To identify the meaning given by teachers to research as part of the process of their own formation; b) To investigate the teacher’s disposition for research; e c) To characterize research practices developed by teachers in the Pedagogy course. The methodology used was the dialectic-hermeneutic circle proposed by Guba and Lincoln. Data collection was done in open interviews applied to the teachers of the Department of Education and Department of Social Sciences and Philosophy. The respondents manifested their thoughts freely about the following themes: teacher’s formation, research in the Pedagogy course, reflexive teacher. First, historical and legal aspects are approached in relation to the insertion of research in the graduation courses in Brazil and the possibilities of its articulation with teaching. Next, the challenges of research in the teacher’s formation courses, the theoretical basis of research and assumptions that orient the application of theories are discussed. Results indicate an insipient practice of collective work in the part of teachers and the need for leadership and dialogue in the level of the department and of the institution. It is suggested that the Theory of Communicative Action can supply the basis for an ideal speech situation as a strategy for building a sense of collectivity which will favor teachers to organize themselves around scientific production.